Probe: Walter J. Ong, St. Ignatius Loyola, and The Constitutions of the Society of Jesus - Farrell, Thomas J. (New Explorations)

(untitled) (New Explorations Association, 2024)
In the first part of this Probe, I explore the American Jesuit Walter J. Ong’s work in relation to the Spanish Renaissance mystic St. Ignatius Loyola (1491-1556), the founder of the Jesuit order, and the history of the Jesuit order. In the second part of this Probe, I discuss Ong’s work in relation to the new 2024 critical edition of The Constitutions of the Society of Jesus, written by St. Ignatius Loyola and his secretary and translated and edited by the American Jesuit theologian Barton T. Geger (born in 1968; doctorate in sacred theology, Universidad Pontifica Comillas in Madrid, 2010) – and published by the Institute of Jesuit Sources at Boston College. Geger wrote his doctoral dissertation on the Constitutions of the Society of Jesus. He explicitly acknowledges (p. 5) that his translation builds on the 1970 translation of the Constitutions from the Spanish by George E. Ganss, S.J. (1905-2000). I style the present essay as a Probe because it is fundamentally exploratory and tentative – much more tentative than my articles and book chapters are.